Just In Time dan Backflush Costing Sebagai Strategi Pengelolaan Biaya Pada Agile Supply Chain - Adinda Putri Asyifa; Aribah Muthi Choironi; Fidia Sanditha; Massagar Al Sya’ban; Rifani Akbar Sulbahri (GLOBAL SCIENTS PUBLISHER, 2026)
This study explores the integration of Just-In-Time (JIT) and backflush costing as cost management strategies within agile supply chains. Employing a Hybrid Systematic Literature Review combining bibliometric analysis and thematic synthesis, eight peer-reviewed articles published between 2020 and 2026 were analyzed. The findings reveal that JIT effectively reduces inventory holding costs and eliminates non-value-added activities through a pull-based production system. Backflush costing complements JIT by simplifying cost recording procedures, improving reporting timeliness, and aligning accounting systems with lean production environments. In the context of agile supply chains, the integration of these two approaches enables companies to obtain more accurate and timely cost information, thereby supporting responsive decision-making. Digital technology serves as a critical enabler that synchronizes physical and information flows in real-time. The study concludes that effective cost management in dynamic business environments requires an integrated approach combining production systems, cost accounting, and digital infrastructure.